Crystallisation characteristics of primary silicon particles in cast hypereutectic Al-Si alloy. (1st April 2013) - Okayasu, M; Takeuchi, S; Shiraishi, T
<x xml:space="preserve">Abstract</x> The crystallisation characteristics of primary silicon particles in a cast hypereutectic Al-Si alloy were examined using various casting processes. The size of the primary silicon particles depends on the cooling rate. However, the primary silicon particles cannot be crystallised completely when the cooling rate is >20 K s−1, since uncrystallised Si atoms migrate to the regions at low cooling rates, producing large primary Si particles. Moreover, turbulent metal flow under conditions of high cooling rate leads to the macrosegregation of the primary Si particles, resulting in poor mechanical properties. From the crystallisation characteristics obtained, a suitable solidification criterion can be proposed.